(Cr, Al)N and (Cr, Al, Mo)N hard coatings for tribological applications under minimum quantity lubrication. (December 2019) - Bobzin, K.; Brögelmann, T.; Kalscheuer, C.; Stahl, K.; Lohner, T.; Yilmaz, M.
Abstract: A promising approach to meet increasing demands on energy efficiency of automotive mobility are triboactive (Cr, Al)N+X (X = Mo, W, Cu) coatings in combination with minimum quantity lubrication (MQL). Within this work, a triboactive (Cr, Al, Mo)N coating and a (Cr, Al)N coating deposited by means of cathodic arc evaporation were investigated in highly-loaded sliding and rolling-sliding contacts under MQL. The uncoated, case hardened steel 16MnCr5E (AISI 5115) was used as reference. Tribological tests were conducted in pin on disk tribometer and twin-disk test rig with a commercial motorcycle oil under MQL. Tribofilms were analyzed by means of Raman spectroscopy. The results show the high potential of (Cr, Al)N and especially (Cr, Al, Mo)N coatings to provide wear reduction and stable operating conditions. Highlights: Analysis of (Cr, Al)N and (Cr, Al, Mo)N coatings under minimum quantity lubrication. Significant wear reduction and stable operating conditions provided by coatings. Coatings provide low friction on same level as injection lubrication. Addition of Mo in (Cr, Al)N leads to reduced friction while keeping wear resistance. High potential of triboactive (Cr, Al, Mo)N coatings for minimum quantity lubrication.